2010
DOI: 10.1088/1751-8113/43/49/495302
|View full text |Cite
|
Sign up to set email alerts
|

Secure key rate of the BB84 protocol using finite sample bits

Abstract: We improve the non-asymptotic key rate shown by Scarani and Renner by proposing several methods to construct tighter conservative confidence intervals of the phase error rate than one previously shown. In addition, we show that the accurate channel estimation method non-asymptotically increases the key rate over the amplitude damping channel as well as the asymptotic case in the BB84 protocol.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…(A.8) Due to the finite post-processing size we include statistical fluctuations of expected QBER and visibility values, given by analysis based on interval estimation. For parameter estimation based on sub-sampling, it is [40,41] δ Q = 1 + η PE (n PP − 1) (η PE n PP ) 2 log 1 PE (A.9)…”
Section: Discussionmentioning
confidence: 99%
“…(A.8) Due to the finite post-processing size we include statistical fluctuations of expected QBER and visibility values, given by analysis based on interval estimation. For parameter estimation based on sub-sampling, it is [40,41] δ Q = 1 + η PE (n PP − 1) (η PE n PP ) 2 log 1 PE (A.9)…”
Section: Discussionmentioning
confidence: 99%
“…However, in the realistic formalism. Scarani et al [31] and Sano et al [32] also treated the finiteness problem only for collective attack. Recently, using Rennerʼs formalism, Tomamichel et al [33] derived an upper bound formula for the security parameter with finite coding length.…”
Section: Introductionmentioning
confidence: 99%
“…However, before this research, the key rates with finite qubits in the B92 protocol had not been reported, as far as the authors know. In this paper, we report the key rates with finite qubits, based on the analytic framework introduced by Scarani and Renner [12] and our previous researches [7], [11]. We stress that the assumption in our paper is the same as [12], and in particular we assume the collective attack instead of the coherent attack.…”
Section: Introductionmentioning
confidence: 99%